A Capital Structure & Cost Efficiency in Selected Listed Financial Firms in Nigeria - John T. Ayoola; Ayokunle O. Odusina (Economy, Business and Development: An International Journal (EB&D), 2023)
The study analyzed the cost effectiveness of a subset of Nigerian listed financial firms and looked at the impact of corporate governance on the subset of listed financial enterprises. Additionally, it evaluated how corporate governance affected how chosen listed financial organizations in Nigeria related to capital structure and cost effectiveness. There were with the intention of supplying details on the interactions between capital structure, corporate governance, and cost effectiveness in a number of Nigerian financial organizations between 2005 and 2020. The study used secondary data from 20 quoted, carefully chosen financial firms in Nigeria and used a descriptive survey design.The annual audited financial statements of the companies were used to collect and analyze data on corporate governance variables like size, membership, independence, and shareholding status; efficiency variables like assets, profit, and share capital; and capital structure variables like long and short term debts. The findings indicated that the deposit money banks in Nigeria had an average cost of efficiency of 54.6%. The capital structure was significantly impacted by corporate governance factors such board size (t= 2.285, p0.05) and board expertise (t=-2.311, p0.05). Finally, the outcome demonstrated that elements of corporate governance such board size (t=-2.807, p 0.05),Board independence and board composition, which acted as intermediary variables between corporate governance and cost effectiveness, were both statistically significant at the 5% level. According to the study's findings, there was a significant association between cost effectiveness, corporate governance, and capital structure.
Keywords: G21; G34; G32; 330; capital structure; corporate governance; cost effectiveness; Financial firms; Nigeria